Syndicated lending - Fight, Andrew (Essential capital markets., 2004)
Syndicated Lending aims to increase the readers awareness of the benefits and risks involved in taking part in the Syndicated Loan market. This book covers:*Who the major players in the syndication loan market are*Why syndication loans are used*Syndication loan structures and documentation*Secondary syndication loan market*Inspired from the basic entry level training courses that have been developed by major international banks worldwide.*Will enable MSc Finance students, MBA students and those already in the finance profession to gain an understanding.